2018
DOI: 10.1097/md.0000000000012334
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of carotid artery ultrasound and hypersensitive C-reactive protein in Type 2 diabetes mellitus patients with acute myocardial infarction in Chinese population

Abstract: Hypersensitive C-reactive protein (hs-CRP) is reported to be significant risk indicators not only for the development of cardiovascular disease, but also for the development or progression of type 2 diabetes. The objective of this study was to analyze the significance of hs-CRP in type 2 diabetes mellitus (T2DM) combined with acute myocardial infarction (AMI).Fifty patients with both T2DM and AMI, 50 patients with T2DM alone, and 50 healthy subjects (control group) were selected.Operating characteristic (ROC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…While in both UA and MI patients, the HsCRP marker could be reported very good indicators for patient's diagnosis, these results agree with (Seyedian et al, 2016) (23) study regarding to UA and agree with (Wang et al, 2020) study (24) which stated that the HsCRP has an important clinical value in the MI diagnosis. Also the present study observed that the HsCRP marker is always significant in the diagnosis between all the groups' combinations, as pointed by the many studies such as (23) , (25) and (24) studies.…”
Section: Discussionsupporting
confidence: 81%
“…While in both UA and MI patients, the HsCRP marker could be reported very good indicators for patient's diagnosis, these results agree with (Seyedian et al, 2016) (23) study regarding to UA and agree with (Wang et al, 2020) study (24) which stated that the HsCRP has an important clinical value in the MI diagnosis. Also the present study observed that the HsCRP marker is always significant in the diagnosis between all the groups' combinations, as pointed by the many studies such as (23) , (25) and (24) studies.…”
Section: Discussionsupporting
confidence: 81%
“…Hypersensitive C-reactive protein (hs-CRP) is a highly sensitive acute inflammatory protein produced by the liver (5), which may be used as an independent risk factor for predicting adverse cardiovascular events. A number of studies have indicated an increase in serum hs-CRP in patients with AMI (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Caregiving could be treated as an external demand and might be appraised as dangerous or challenging, what could be important in terms of psychometric evaluations. 20,26…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Interleukin-6 induces the production of C-reactive protein (CRP) in the liver, and a high serum CRP concentration is a risk factor for many diseases, including cardiovascular diseases and type 2 diabetes. 20 Therefore, this immune dysregulation could be the mechanism behind the physical health risks associated with caregiving. 18,19…”
mentioning
confidence: 99%